Related Factors to the Use of Oral Health Services amongst Population Aged 6 to 15 Years in Colombia (2014)
ABSTRACT: The objective of this study was to analyze related factors to the use/no use of oral health services amongst children aged 6 to 15 in Colombia. Cross-sectional analysis with the information provided for the 2007 National Public Health Survey. Exposure variable: Use of oral health services. Health status variables: Self-rated health, oral health problems, oral pain, dental caries, gum bleeding. Explicative variables: Sex, age and ethnic origin. A descriptive study of the variables was carried out. Logistical regression was used to estimate the relationship between the category “never had an oral health visit” and each explicative and general and oral health status indicators, first crudely and after adjusting for other variables (Odds Ratio OR, 95% Confidence Intervals 95%CI). Analyses were conducted separately for men (M) and Women (W). The prevalence of use of health services is higher in people reporting not to belong to an ethnic group, those reporting dental problems, oral-dental pain, dental caries and gum bleeding (statistically significant differences p<0.05). After adjusting for control variables people aged 6 to 8 (W: OR 2.18 95%CI 1.87–2.53), those reporting to belong to an ethnic group (M: 3.01 95%CI 2.44–3.71; W: OR 3.59 95%CI 2.86–4.51) and those reporting poor self-rated health (W: OR 1.44 95%CI 1.25–1.66) were more likely to report “have never been to a dental visit”. Inequalities in use of oral health services in Colombia amongst study population were found in younger children and those belonging to minority ethnic groups. These findings are linked to barriers to health services accessibility.